2005
DOI: 10.1073/pnas.0503460102
|View full text |Cite
|
Sign up to set email alerts
|

RPE65 is the isomerohydrolase in the retinoid visual cycle

Abstract: RPE65 is an abundant protein in the retinal pigment epithelium. Mutations in RPE65 are associated with inherited retinal dystrophies. Although it is known that RPE65 is critical for regeneration of 11-cis retinol in the visual cycle, the function of RPE65 is elusive. Here we show that recombinant RPE65, when expressed in QBI-293A and COS-1 cells, has robust enzymatic activity of the previous unidentified isomerohydrolase, an enzyme converting all-trans retinyl ester to 11-cis retinol in the visual cycle. The i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
375
1
2

Year Published

2007
2007
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 453 publications
(387 citation statements)
references
References 31 publications
(30 reference statements)
9
375
1
2
Order By: Relevance
“…ments (5)(6)(7). In the present study, we have demonstrated that the RPE65 in chicken eyes has significantly higher enzymatic activity, when compared with that in human and bovine eyes.…”
Section: Discussionmentioning
confidence: 51%
See 1 more Smart Citation
“…ments (5)(6)(7). In the present study, we have demonstrated that the RPE65 in chicken eyes has significantly higher enzymatic activity, when compared with that in human and bovine eyes.…”
Section: Discussionmentioning
confidence: 51%
“…Confirmed human and chicken RPE65 cDNAs were cloned between the NotI and HindIII sites of the pShuttle-CMV vector (Qbiogene, Montreal, Canada) for construction of adenoviruses. Preparations, amplification, and titration of the recombinant adenoviruses were performed as described previously (5).…”
Section: Methodsmentioning
confidence: 99%
“…It has been reported that RPE65 is involved in the isomerization reaction that produces 11-cis-retinol and that retinyl esters are the preferred substrates for this reaction (51)(52)(53). It has also been proposed that palmitoylation of RPE65 by LRAT regulates its subcellular localization and its ligand binding selectivity versus retinol or retinyl esters (54).…”
Section: Discussionmentioning
confidence: 99%
“…The resulting all-trans RAL is first reduced to all-trans ROL by an NADPH-dependent dehydrogenase (Cideciyan et al, 2000;Lion et al, 1975;Rattner et al, 2000;Suzuki et al, 1993), and then transported from the photoreceptor to the second compartment involved in visual pigment recycling, the RPE. Upon arrival in RPE cells, all-trans ROL is esterified into retinylesters (REs) by the lecithin:retinol acyltransferase LRAT (Mondal et al, 2000;Ruiz et al, 1999;Saari and Bredberg, 1989;Saari et al, 1993), and then isomerized to 11-cis ROL by the isomerase RPE65 (or Isomerase I) (Gollapalli and Rando, 2003;Jin et al, 2005;Moiseyev et al, 2005;Redmond et al, 2005). Finally, 11-cis ROL is oxidized to 11-cis RAL by a retinol dehydrogenase (Cideciyan et al, 2000;Driessen et al, 1997;Gamble et al, 2000;Haeseleer et al, 1998;Lion et al, 1975;Simon et al, 1999;Suzuki et al, 1993).…”
Section: Canonical Retinoid Recycling In Vertebrate Eyesmentioning
confidence: 99%